(untitled) - Casey, Maurice (United Kingdom, 2002)
This is the first book to examine the Aramaic dimension of Q since the Aramaic Dead Sea scrolls made such work more feasible. Maurice Casey reconstructs sources of Q--material found in the Gospels of Matthew and Luke and not taken from the Gospel of Mark--and replaces the conventional model of Q as a single Greek document with something more complex. The reconstruction and interpretation of the Aramaic sources raises the level of proof that Jesus said and did some of the things attributed in our earliest sources.
Keywords: Văn học Ả Rập,Q hypothesis (Synoptics criticism),Aramaic literrature; Giả thuyết Q,Mối liên hệ với Tân Uớc,Relation to the New Testament